TOWARD QUANTITATIVE OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY: Visualizing Blood Flow Speeds in Ocular Pathology Using Variable Interscan Time Analysis. (December 2016) - Ploner, Stefan B.; Moult, Eric M.; Choi, WooJhon; Waheed, Nadia K.; Lee, ByungKun; Novais, Eduardo A.; Cole, Emily D.; Potsaid, Benjamin; Husvogt, Lennart; Schottenhamml, Julia; Maier, Andreas; Rosenfeld, Philip J.; et al.
Abstract : Purpose: Currently available optical coherence tomography angiography systems provide information about blood flux but only limited information about blood flow speed. The authors develop a method for mapping the previously proposed variable interscan time analysis (VISTA) algorithm into a color display that encodes relative blood flow speed. Methods: Optical coherence tomography angiography was performed with a 1, 050 nm, 400 kHz A-scan rate, swept source optical coherence tomography system using a 5 repeated B-scan protocol. Variable interscan time analysis was used to compute the optical coherence tomography angiography signal from B-scan pairs having 1.5 millisecond and 3.0 milliseconds interscan times. The resulting VISTA data were then mapped to a color space for display. Results: The authors evaluated the VISTA visualization algorithm in normal eyes (n = 2), nonproliferative diabetic retinopathy eyes (n = 6), proliferative diabetic retinopathy eyes (n = 3), geographic atrophy eyes (n = 4), and exudative age-related macular degeneration eyes (n = 2). All eyes showed blood flow speed variations, and all eyes with pathology showed abnormal blood flow speeds compared with controls. Conclusion: The authors developed a novel method for mapping VISTA into a color display, allowing visualization of relative blood flow speeds. The method was found useful, in a small case series, for visualizing blood flow speeds in a variety of ocular diseases and serves as a step toward quantitative optical coherence tomography angiography. Abstract : The authors developed a methodology for visualizing blood flow speeds in ocular pathology using optical coherence tomography angiography and variable interscan time analysis.